Brachytherapy and endoresection for choroidal melanoma: a cohort study. Issue 1 (16th October 2013) - Rice, James C; Stannard, Clare; Cook, Colin; Lecuona, Karin; Myer, Landon; Scholtz, Raoul P
Abstract : Aim: To report and compare the outcomes of brachytherapy and endoresection in the conservative treatment of medium sized choroidal melanoma. Methods: A retrospective cohort study. Medium tumours were defined as 2.5–10 mm in height and less than 16 mm in the widest diameter. Consecutive patients undergoing brachytherapy at Groote Schuur Hospital were compared with a cohort undergoing endoresection from a national database. Results: 148 brachytherapy and 22 endoresection patients were followed for a median of 55.4 and 62.4 months, respectively. Tumours undergoing endoresection were thicker (7.3 vs 4.9 mm, p<0.001, Wilcoxon rank-sum test) and further from the fovea (5.2 vs 3.7 mm, p=0.05, Wilcoxon rank-sum test) than those treated with brachytherapy. Visual acuity of 6/18 or better was maintained in 41% of the endoresection group and 35% of the brachytherapy group. The likelihood of achieving a final visual acuity of better than 2/60 was 22% higher in the endoresection group (risk ratio 1.22, 95% CI 1.02 to 1.28, p=0.034). Rates of local recurrence (18.2% vs 14.9%, p=0.75) and metastases or death (18.2% vs 14.2%, p=0.75) were higher in the endoresection group, and the enucleation rate was lower in this group (4.6% vs 10.8%, p=0.70) but these were not statistically significant. Conclusions: The outcomes observed in this small cohort of endoresection patients suggest that endoresection of selected tumours may achieve better visual outcomes than brachytherapy. Rates of local recurrence, enucleation and metastases following endoresection require further research. Local recurrence is likely to be influenced by consolidation treatment methods.